Strategi Pemasaran Digital yang Efektif dalam Upaya Peningkatan Daya Saing UMKM Keduemas Kecamatan Kelapa Dua Kabupaten Tangerang Provinsi Banten - Amar, Abu; Affandi, Awaludin; Sunandar, Andi; Azizah, Monica Bramel Ari; Sahroni, Sahroni; Arianto, Nurmin (Jurnal PKM Manajemen Bisnis, 2024)
Advances in digital technology have opened up vast opportunities for MSMEs to expand their marketing reach and improve their competitiveness. However, many MSMEs still do not optimally utilize the potential of digital technology. One of the MSME groups facing this challenge is the KEDUEMAS MSME in Kelapa Dua District, Tangerang Regency, Banten Province. This Community Service Program (PKM) aims to improve the ability of micro, small, and medium enterprises (MSMEs) in Kelapa Dua District, Tangerang Regency, to implement effective digital marketing strategies. This is very important considering the development of technology and the shift in consumer behavior that is increasingly digital. Through this PKM program, training and mentoring will be provided to KEDUEMAS MSME players related to digital marketing strategies, such as the use of social media, websites, search engine optimization (SEO), and marketing via email. The goal is for MSMEs to increase their knowledge and ability to utilize technology to expand market reach and increase sales. In addition, this PKM program will also help KEDUEMAS MSMEs increase their competitiveness in the digital era through the use of technology and effective digital marketing strategies. We will identify the needs and problems of KEDUEMAS MSMEs, design appropriate digital marketing strategies, and assist them in implementing them. By achieving these goals, it is expected that KEDUEMAS MSMEs can increase their marketing reach, brand awareness, and ultimately increase product sales and competitiveness in the midst of increasingly fierce digital market competition. This will also contribute to regional economic growth and empowerment of MSMEs as the backbone of the national economy.